If Motivation Was a Key Factor in Aerobic Performance in Tropical Climate? - Coudevylle, Guillaume R.; Sinnapah, Stéphane; Collado, Aurélie; Fenouillet, Fabien; Hue, Olivier; Parrat, Matthieu; Robin, Nicolas (Frontiers in Psychology, 2021)
This mini review examines the impact of tropical climate (TC) on motivational factors during aerobic performance and proposes the tracks of an integrative theoretical model to better understand the direct and indirect motivational mechanisms that can operate on athletic performances. TC is detrimental for aerobic performance and, although it clearly induces physiological constraints, these do not seem to be the only factors that explain the performance decline. Indeed, TC performance researchers have developed a theory of anticipation, which suggests that the brain commands a reduction in effort to protect the body from probable harm and heatstroke risk. The objective of this mini review is thus to examine the possibility that motivation may be a key factor in TC performance. The main psychological impacts of TC on aerobic performance are reviewed and an integrative theoretical model is presented that may help to better understand the mechanisms of motivation.